Respuesta :
Substitution would be a great approach to solving this system, because the first equation defines y as x - 10 and you can thus substitute x - 10 for y in the second equation:
2x + (x - 10) = 4
Then 3x - 10 = 4, and 3x = 14. Solving for x: x = 14/3.
Since y = x-10, subst. 14/3 for x to find y: y = 14/3 - 30/3 = -16/3
The solution is (14/3, -16/3).
2x + (x - 10) = 4
Then 3x - 10 = 4, and 3x = 14. Solving for x: x = 14/3.
Since y = x-10, subst. 14/3 for x to find y: y = 14/3 - 30/3 = -16/3
The solution is (14/3, -16/3).